(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Marketers and advertisers in the city have little choice but to use social media to spread theword about their wares, thanks to the explosion of internet use in recent years. The use of social media ofall kinds has exploded in Indore in recent years. In the past, advertisers and marketers could reach theirtarget audiences and compete with one another in an advertising war via the use of conventionalmedia. As Facebook has expanded, so have the methods used to promote its users’ goods and services.Studies of Facebook advertisements and the level of user engagement they inspire are still in theirinfancy in Indore.Preparedness for Facebook ads among chronic social media users A total of 178 young people fromIndore City were surveyed. The study’s young participants in Indore showed not just a high level offamiliarity with Facebook ads, but also a positive attitude toward those they saw. The current researchconcurs with its predecessors in finding that advertising on social media is more engaging and forceful.Facebook ads are more noticeable and may be strategically placed to reach a certain demographic.Compared to other social media platforms, more detailed but concise messages may be communicated.